The relationship between prevalence of dental anxiety and dental caries: cross-sectional study - Dikmen, Benin; Saral, Isik; Ucuncu, Musa Kazim; Yildiz, Esra; Ozel Yildiz, Sevda (Brazilian Dental Science, 2022)
Objective: This cross-sectional study aimed to assess level of DA among dental students in different grades and patients and to evaluate associations between DA and presence of dental caries. Material and Methods: Both four hundred all-grade dental students of Istanbul University and patients of Istanbul University Hospital were included in the study after random selection. Data regarding gender, oral hygiene habits, frequency of dental visits, and educational level were obtained via questionnaire. DA of participants were measured using both Modified Dental Anxiety Scale (MDAS) and Dental Fear Survey (DFS). The prevalence of caries was determined using International Caries Detection and Assessment System Criteria (ICDAS). Data were analyzed using Kruskal-Wallis, Mann-Whitney U and Chi square tests. Results: Female patients and female 4th-year students had significantly higher MDAS scores (p<0.05). First-year students had significantly higher MDAS and DFS scores than 4th and 5th-year students (p<0.05). Patients who had caries and brushed their teeth less than twice a day had significantly higher MDAS scores (p<0.05). Among 3rd-year students, individuals who visited dentist regularly had lower MDAS scores (p<0.05). Conclusion: DA among senior dental students was lower than that in younger students with an increase in knowledge about dentistry. Tooth brushing frequency and caries prevalence was associated with DA in patient group. No association was found between DA and frequency of dental visits, except in 3rd-year students. KEYWORDS Dental anxiety; Dental caries; Dental student; Prevalence.